Pengaruh Konsumsi Energi Listrik Kawasan Permukiman Terhadap Emisi Karbon Dioksida Kota Semarang - Tusiana Wismandani; Widjonarko Widjonarko (Jurusan Perencanaan Wilayah dan Kota, 2017)
Population growth in Semarang City increases the need of settlements, which have many activities that need electricity power generated from the power plant by burning a huge amount of fossil fuel. Carbon dioxide was a by-product of the burning process, and also the most abundant Green House Gas contained in the atmosphere. This research expected to dicover the influence of electricity consumption towards carbon dioxide emissions particularly in Semarang City, by indetifying the electricity consumption of the four settlements sectors: household, industry, commercial, and governmental. Then, analyzing their correlation and effect towards carbon dioxi de emissions partially using multiple regression method, and comprehensively using simple linear regression. The household sector has the highest electricity consumption, followed by industry, commercial, and governmental sector. Yet, it also has numerous consumers which caused it’s consumption per-consumer to be the lowest amongst all of the sectors. Conversely, industrial sector has the highest consumption per-consumer since it has high electricity usage yet a fewest consumers. The multiple regression analysis showed that sectoral electricity consumption didn’t represent a valid result because there was a multicollinearity between the independent variables. Whilst the simple regression discovered that comprehensive electricity consumption gave a significant effect to the carbon dioxide emissions, where 1% increasement of electricity usage also increase upto 1.421.525,52 ton carbon dioxide emissons.